Factors Influencing Brand Image and Customer Repurchase Intention: The Case of Coffee Chain Shops Located in Gas Service Stations in Bangkok - Ratasuk, Akaraphun; Gajesanand, Sunanta (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
This research investigated the contribution of marketing factors, including perceived product quality, perceived service quality, store atmosphere, perceived price, location, and promotion, to brand image and customer repurchase intention in chain coffee shops located in gas service stations in Bangkok. Survey data were collected from 523 customers of 30 chain coffee shops located in gas service stations throughout the Bangkok area and computed using partial least squares structural equation modeling. The results indicated that perceived product quality, store atmosphere, perceived price, promotion, and brand image were crucial for the development of customer repurchase intention. The results also showed that only perceived product quality and store atmosphere could promote repurchase intention through enhancing brand image. Since the contributions of the marketing factors to brand image and repurchase intention in the context of chain coffee shops located in gas service stations have not yet been explored, this research has provided additional evidence to the existing coffee chain, brand image, and customer repurchase intention research